Pemberian Enzim Papain pada Pakan Komersil Terhadap Pertumbuhan dan Efisiensi Pakan Ikan Kerapu Macan (Epinephelus fuscoguttatus) - Fadli, Jauharul; Sunaryo, Sunaryo; Djunaedi, Ali (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Tiger grouper (E.fuscoguttatus) is one of the coral reef fishes, who has significant economical value. Relatively expensive value and highly demand of this species on the market prospective make a lot of fish has been developed by fishermen through aquaculture. This study aimed to determine the effect of the enzyme papain in commercial feed on the growth and feed efficiency of Tiger Grouper (E.fuscoguttatus). This study was conducted at the Center for Development of Brackish Water Aquaculture (BBPBAP) Jepara in June-August 2012. The method, that was used in this study was experimental with completely randomized design (CRD). This study used 4 treatments, each was replicated 3 times. Treatment was the use of enzyme papain in the commercial feed with a protein content of 46-48% as much as 3%in treatment A, 4% in treatment B, 5% in treatment C, and 0% as control in treatment D. The respon of treatment showed significant by different on growth. The and in grafik was reached by treatment C ( the used of enzyme papain 5% in the artificial feed), i.e : 3,24% day -1, and than followed by treatment B of 3,15% day -1, treatment A of 3,03 day -1, and treatment D as control of 2,92% day -1. The results were obtained in this study showed that the use of the enzyme papain in artificial diets with specific concentration had a positive by effect on growth and feed efficiency. Papain enzyme capable of hydrolyzing the protein in the feed is higher amino acid to be absorbed and utilized for growth.